The Indonesian economy crisis causes, consequences and lessons - Hill, Hal (Institute of Southeast Asian Studies (ISEAS), 1999)
This book describes and analyzes Indonesia's most serious economic crisis, against the general backdrop of economic decline in Southeast Asia.